Two 1D Silver(I) Coordination Polymers with 1, 3‐Bis(4‐pyridyl) propane and Aromatic Carboxylate Anions: Synthesis, Structure and Photocatalytic Behavior. Issue 34 (8th September 2021) - Kulovi, Somnath; Nandi, Laxmikanta; Puschmann, Horst; Zangrando, Ennio; Dalai, Sudipta
Abstract: Two coordination polymers, [Ag(bpp)]6 (tma)2 .28(H2 O)n (1 ) and [Ag4 (bpp)4 (bda)2 ].12(H2 O)n (2 ) (where bpp=1, 3‐bis(4‐pyridyl) propane, H3 tma=trimesic acid, H2 bda= 1, 3‐benzenediacetic acid), have been synthesized and structurally characterized. In both the compounds the metal ions are connected by bridging dipyridine ligands to form cationic undulated 1D coordination polymers [Ag(bpp)]n counterbalanced by the organic anions. However, in 2 the bda anions participate in metal coordination connecting the polymers in pair. It is worth of note that six and four crystallographic independent Ag(bpp) units are present in the unit cell of 1 and 2, respectively, a feature likely affected by the conformational freedom of bpp ligands, although experimental conditions, solvent and packing effect cannot be ruled out. In both the compounds the crystal packing shows an extensive network of H‐bonds realized by the numerous water molecules and the anionic organic species. The band gap energies of 1 and 2 were calculated in order to explain their activity towards the degradation of toxic methylene blue dye, and compound 1 was found to be more efficient for this purpose. Abstract : Two new photocatalytic, extensively hydrogen bonded, silver(I) coordination polymers have been synthesized. The photocatalytic activity was investigated against the degradation of a toxic methylene blue dye.